Evaluation of the development program anemon dive club - Noprian Tri Handoko; Achmad Sofiyan Hanif; Yasep Setiakarnawijaya (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2022)
This study aims to evaluate the coaching program of the Anemon Dive Club, which is a sports association that fosters and develops swimming sports in Indonesia. In this evaluation, the study used a survey method using the CIPP model, namely, Context, Input, Process, Product. From the results of this study it is concluded that: the context stage, the Anemon Dive Club coaching program is considered very good, the implementation carried out is according to the Vision and Mission. Then the Goals and Strategic Plans serve as guidelines and references in the implementation of the Anemone Dive Club program. The input stage, which involves association performance, coaching and training programs, athletes, the availability of coaches, infrastructure and funding sources is considered Very Good, which is 83.5%. The process stage includes the implementation of the coaching program and the effectiveness of the program implementation is considered good, with an average rating of 82.98%. The last stage, namely the stage of the product being evaluated is the achievement of targets regarding the assessment of the pattern of coaching carried out. Then the next achievement in the academic field by participating in and winning events in diving, athletes who excel can enter excellent schools with an achievement pathway, so that in addition to sports achievements, academic achievements can also be obtained.